2022
DOI: 10.1002/bdr2.2099
|View full text |Cite
|
Sign up to set email alerts
|

Animal evidence considered in determination of cannabis smoke and Δ9‐tetrahydrocannabinol as causing reproductive toxicity (developmental endpoint); Part I. Somatic development

Abstract: Objectives: On December 11, 2019, California's Developmental and Reproductive Toxicant Identification Committee (DARTIC) met to consider the addition of cannabis smoke and Δ 9 -THC to the Proposition 65 list as causing reproductive toxicity (developmental endpoint). As the lead state agency for implementing Proposition 65, the Office of Environmental Health Hazard Assessment (OEHHA) reviewed and summarized the relevant scientific literature in the form of a hazard identification document (HID). Here we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Reproductive and developmental toxicology findings in ∆9-THC-treated animals have been discussed in FDAapproved product labels and the published literature (for review see (Campbell et al, 2022;Iyer et al, 2022;Niknam et al, 2022), According to the package insert for the Marinol product, data from embryo-fetal toxicology studies in mice (15 to 450 mg/m 2 ) and rats (74 to 295 mg/m 2 ) demonstrated that teratogenic effects were not produced up to maternally toxic doses and embryo-and fetal-lethal doses (Marinol). Pregnant rodents treated with ∆9-THC were observed with decreased weight gain values.…”
Section: Iiib5 Reproductive and Developmental Toxicology Studiesmentioning
confidence: 99%
“…Reproductive and developmental toxicology findings in ∆9-THC-treated animals have been discussed in FDAapproved product labels and the published literature (for review see (Campbell et al, 2022;Iyer et al, 2022;Niknam et al, 2022), According to the package insert for the Marinol product, data from embryo-fetal toxicology studies in mice (15 to 450 mg/m 2 ) and rats (74 to 295 mg/m 2 ) demonstrated that teratogenic effects were not produced up to maternally toxic doses and embryo-and fetal-lethal doses (Marinol). Pregnant rodents treated with ∆9-THC were observed with decreased weight gain values.…”
Section: Iiib5 Reproductive and Developmental Toxicology Studiesmentioning
confidence: 99%
“…Cannabis use during pregnancy can also harm fetal and long-term development [8]. Babies exposed to cannabis prenatally are more likely to have restricted growth in utero, lower birth weight, and smaller head circumference [9,10]. In addition, emotional processing, sleep, aggressive behavior, and the ability to pay attention may be affected in infants [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal cannabis exposure also lowers immune response to viruses and causes ventricular septal defects [13,14]. Children exposed to cannabis in utero are at a greater risk for delinquent behavior, lower IQ, decreased attention span, and using cannabis and nicotine products themselves [9,10]. While many of the same toxic chemicals in tobacco smoke such as heavy metals, carbon monoxide, benzene, and formaldehyde are found in cannabis smoke, some are unique cannabinoid compounds found specifically in cannabis smoke such as tetrahydrocannabinol (THC), the psychoactive chemical in cannabis [15].…”
Section: Introductionmentioning
confidence: 99%